A new eriophyid mite-borne membrane-enveloped virus-like complex isolated from plants - Skare, Joanna M.; Wijkamp, Ineke; Denham, Ivey; Rezende, Jorge A.M.; Kitajima, Elliot W.; Park, Jong-Won; Desvoyes, Benedicte; Rush, Charles M.; Michels, Gerald; Scholthof, Karen-Beth G.; Scholthof, Herman B. (Virology (New York, N.Y.), 2006)
A decade ago, a new mite-transmitted disease was described on wheat ( Triticum aesativum) and maize ( Zea mays) that due to its geographical location was referred to as High Plains Disease (HPD). To determine the etiology, we established colonies of HPD pathogen-transmitting eriophyid wheat curl mites ( Aceria tosichella) on wheat plants for maintenance of a continuous source of infected material. Analyses of nucleic acid obtained from infected plants showed the presence of HPD-specific RNAs ranging from 1.5 to 8 kilobases, but comparisons between the sequence of cDNAs and the databases did not reveal any clear identity with known viruses. We demonstrate that a diagnostic HPD-specific 32-kDa protein that accumulates in plants is encoded by a small RNA species (RNA-s). Upon infestation of upper wheat parts with viruliferous mites, the RNA-s encoded protein becomes detectable within a few days in the roots, indicative of an effective virus-like mode of transport. Membranous particles, resembling those observed in thin sections of infected plants, were isolated and shown to envelope a thread-like ribonucleoprotein complex containing the RNA-s encoded 32-kDa protein. This complex was associated with single-stranded (−)-sense RNAs, whereas free (+)-sense RNA was only detected in total RNA of infected plants. Based on the collective properties, we conclude that HPD is caused by a newly emerged mite-borne virus, for which we propose the name Maize red stripe virus (MRStV).